CONSUMER PROTECTION AND FINTECH COMPANIES IN INDONESIA: INNOVATIONS AND CHALLENGES OF THE FINANCIAL SERVICES AUTHORITY - Ika Atikah (Jurnal Hukum dan Peradilan, 2020)
The article has questions from the background of the research as follows: how to protect consumers fintech transactions from financial technology companies? What are the innovations and challenges of the financial services authority in overseeing and issuing regulations related to fintech? The research method used is normative with the statute approach and conceptual approach. The technique of collection primary legal is carried out by collecting OJK regulations regarding fintech companies, and consumer protection. Meanwhile, the technique of collection secondary legal is the concept or theories related to the main issue complete with bibliography. The Results that found are the fintech companies must be registered in the financial services authority by obeying and implementing OJK regulations. Innovation that OJK did enact Supervisory Technology (Suptech) to develop the financial technology (fintech) corporate ecosystem that is included in the realm of Digital Financial Innovation (IKD) on the OJK portal with the name Gerbang Elektronik Sistem Informasi Keuangan Digital. OJK also established the Innovation Center or Fintech Center in 2018. Challenges OJK must face: fintech lending is to create a balance between increasing financial inclusion and risk management, improving people’s understanding of fintech services, infrastructure, cybersecurity and data protection for consumers and fintech must collect more consumer data so that the lending and borrowing process becomes more efficient and effective.